Pengembangan kompetensi guru pendamping anak usia dini berkebutuhan khusus dengan autism spectrum disorder (ASD) - Cahyaningsih, Sri Lestari; Nasir , Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2024)
A teacher is a person who has academic competence and qualifications as a learning agent, provides knowledge, provides guidance and direction to students according to their scientific field, and will make students intelligent, smart, able to understand the knowledge that has been taught and has broad and critical thinking insights. Shadow teachers are teachers who work directly and face to face with children and assist the class teacher. The presence of a shadow teacher is very helpful in conditioning the class when the class teacher is providing lessons and explanations to students. Shadow teacher will deal with one student with special needs. Competency standards for shadow teachers meet three criteria, pedagogical standards, personality standards and professional standards. To become an shadow teacher, you need a supportive academic education, having an educational certificate at the level of D-IV/S1 PGTK or psychology or other relevant education. Or a diploma D-II PGTK from an accredited study program. The need for shadow teachers who are really needed by inclusive schools is not yet balanced with the number of students with special needs in schools. Apart from that, shadow teachers have not been provided with adequate training. This research was carried out through a literature review with a qualitative approach. The systematic review process uses various literature reviews and articles from national scale scientific journals. The analysis obtained from the study is that training is needed to support the competence of accompanying teachers in the process of teaching students with special needs. The training required is 1) explanation of inclusive education, 2) children with special needs and their characteristics and diversity, 3) growth and development of children with special needs, 4) how to provide stimulation to children with special needs, 5) how to care for and protect children with special needs, 6 ) create an individual learning program. The number of shadow teachers currently in Samarinda city inclusive schools is not yet comparable to the inclusion schools that have been decreed by the Mayor.